Enhanced thermal imaging of wound tissue for better clinical decision making. (11th May 2017) - Keenan, Ellen; Gethin, Georgina; Flynn, Louisa; Watterson, David; O'Connor, Gerard M
Abstract: Infrared cameras are increasingly applied in clinical applications as they allow fast, inexpensive and non-contact temperature measurements. As abnormal heat distribution can indicate illness, infrared cameras have been applied in the prediction, diagnosis and monitoring of medical conditions. Current practices, however, often overlook the importance of emissivity when taking thermal measurements. The consensus is that human skin has an emissivity of 0.98 but this value varies between individuals, areas examined, and if the skin is damaged. In particular, further research should be conducted on the emissivity variations of wounds. Objective: This research investigated the emissivity variation of chronic wounds and its effect on thermal measurements. Eleven patients with non-infected foot ulcers were recruited. Three non-diabetic wounds were also investigated in a clinical setting. Approach: A reflectance based method was used which involved alternating shades at different temperatures over the region of interest. Based on the change in the thermal images, emissivity was calculated at each pixel. Main Results: Overall, it was found that the emissivity of wounds was similar or slightly higher to intact skin (range 0.01–0.03 higher with an average value of 0.97  ±  0.03), with lower values at wound edges (on average 0.02 lower than intact skin). Correcting for emissivity resulted in an average temperature difference of 0.83% in the thermal images. Significance: Despite the similarity in emissivity, the difference between the original thermal image and the emissivity corrected thermal image in some cases was substantial. These differences could prove significant in clinical evaluations, indicating the need to incorporate emissivity measurement into standard protocol to ensure utmost accuracy.